1999
DOI: 10.1111/j.1651-2227.1999.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective audit of paediatric colonoscopy under general anaesthesia

Abstract: Colonoscopy in children is frequently performed using intravenous sedation. Traditionally, there have been few advocates of general anaesthesia and some have regarded colonoscopy conducted in this way as potentially more hazardous. The aim of this study was to undertake a prospective audit of paediatric colonoscopy carried out under general anaesthesia. The details of all children referred for colonoscopy during a 3.5‐y period were collected prospectively and the safety and efficacy of performing colonoscopy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In Asia, the prevalence rates of positive diagnostic findings were 45.8, 50.6, and 70.5% of studies from Korea, Hong Kong and South China, respectively [1315]. In the United Kingdom, 62% of colonoscopies performed in children younger than 16 years old had abnormal findings [16]. Lissy et al reported that diagnostic colonoscopy revealed abnormalities in 80% of children referred with rectal bleeding [17].…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the prevalence rates of positive diagnostic findings were 45.8, 50.6, and 70.5% of studies from Korea, Hong Kong and South China, respectively [1315]. In the United Kingdom, 62% of colonoscopies performed in children younger than 16 years old had abnormal findings [16]. Lissy et al reported that diagnostic colonoscopy revealed abnormalities in 80% of children referred with rectal bleeding [17].…”
Section: Discussionmentioning
confidence: 99%
“…The findings were as follows: normal (41%), other (stricture/stenosis, tumor, anatomic deformity, Crohn disease, colitis, fissure/fistula/melanosis) (27%), mucosal abnormality (including pouchitis and proctitis) (21%), polyp (9%), and multiple polyps (2%). Others have reported similar normal rates of 38% to 45% (4)(5)(6). Pediatric colonoscopy is not without risk and complication rates have been up to 1.1% with perforation rates of 0.01% to 0.11% with no reported deaths (4,5,7,8).…”
mentioning
confidence: 91%
“…Others have reported similar normal rates of 38% to 45% (4)(5)(6). Pediatric colonoscopy is not without risk and complication rates have been up to 1.1% with perforation rates of 0.01% to 0.11% with no reported deaths (4,5,7,8).…”
mentioning
confidence: 91%
“…These complications included one hemorrhage requiring transfusion and one perforation. In the second largest study, Stringer et al 2 prospectively described a series of 250 flexible colonoscopies done in the United Kingdom during a 3.5-year period with no adverse events. Several other studies reported complications (Table 1) in pediatric colonoscopy, but the majority of these studies examined a small number of procedures.…”
mentioning
confidence: 99%